2006
DOI: 10.1182/blood-2006-02-005892
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD34+ cells, pulmonary hypertension, and myelofibrosis

Abstract: Response:Deferasirox (ICL670) effectively reduces liver iron concentration, whether assessed by biopsy or SQUIDWe thank Drs Fischer, Harmatz, and Nielsen for their letter and interest in our paper. In this study, liver iron concentration (LIC) was assessed either by biopsy (84% of patients) or superconducting quantum interference device (SQUID; 16%, primarily children and adults with contraindications to biopsy). SQUID assessments were performed at 3 centers (in Italy, Germany, and the US); baseline and end-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…In this study patients with primary myelofibrosis and PH had higher bone marrow microvessel density and vascular endothelial growth factor levels suggesting the presence of a proangiogenic phenomenon [98,99]. Other studies demonstrated that distinctive features of myelofibrosis associated with PH include normal or low circulating CD34 cell count, polyclonal platelets and granulocytes, absence of peripheral blood dacrocytes and the JAK2 1849G.T(V617F) mutation [100,101].…”
Section: Aetiologysupporting
confidence: 54%
“…In this study patients with primary myelofibrosis and PH had higher bone marrow microvessel density and vascular endothelial growth factor levels suggesting the presence of a proangiogenic phenomenon [98,99]. Other studies demonstrated that distinctive features of myelofibrosis associated with PH include normal or low circulating CD34 cell count, polyclonal platelets and granulocytes, absence of peripheral blood dacrocytes and the JAK2 1849G.T(V617F) mutation [100,101].…”
Section: Aetiologysupporting
confidence: 54%
“…In this study, patients with primary myelofibrosis and PH had higher bone marrow microvessel density and vascular endothelial growth factor levels, suggesting the presence of a pro-angiogenic phenomenon [14,71]. Other studies demonstrated that distinctive features of myelofibrosis associated with PH include normal or low circulating CD34 cell count, polyclonal platelets and granulocytes, the absence of peripheral blood dacrocytes and the JAK2 1849G>T(V617F) mutation [72,73].…”
Section: Precapillary Pulmonary Hypertensionsupporting
confidence: 53%
“…2 Distinctive features of MF associated with PAH include normal or low circulating CD34 cell count, polyclonal platelets and granulocytes, absence of peripheral blood dacrocytes and the JAK2 1849G>T(V617F) mutation. 3,4 We have recently shown that there is an overexpression of pericytes around the wide and tortuous capillaries in the bone marrow of patients with PMF, PPMF and PTMF, 5 i.e. the proportion of pericyte covered vessels was significantly higher in these patients as compared to controls.…”
Section: Angiogenesis In Pulmonary Hypertension With Myelofibrosismentioning
confidence: 95%